Employee Satisfaction as a Mediating Variable between Talent Management and Organizational Performance - Devi Alviani; Riky Perdana (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2026)
The current literature exhibits notable gaps, driven by inconsistent empirical findings regarding the relationship between talent management and organizational success, alongside a shortage of empirical data from learning organizations within emerging markets. To bridge these gaps, this investigation explores the direct and indirect influences of talent management on institutional performance—hypothesizing employee job satisfaction as a key mediator, within an educational context. The target population encompassed both teaching faculty and administrative staff from senior high and vocational institutes throughout Riau Province. Of the 300 questionnaires distributed, 259 valid responses were retrieved, representing an 86.3% response rate. Data analysis was executed using partial least squares structural equation modeling via PLS 3.0 (SEM-PLS 3.0). The empirical results reveal that strategic talent management practices simultaneously enhance organizational performance and foster higher levels of employee satisfaction and commitment. In particular, when staff members feel recognized and supported by these initiatives, their job satisfaction increases. This heightened satisfaction, in turn, translates into sustained superior performance metrics that drive overall institutional success. Consequently, employee satisfaction functions as an essential mediating mechanism that strengthens the positive outcomes of talent management on organizational success, highlighting its critical importance in sustaining a productive and thriving workplace.